Psychosocial factors predicting first-year college student success - Krumrei, Elizabeth J.; Newton, Fred B.; Kim, Eunhee; Wilcox, Dan (My University, 2013)
This study made use of a model of college success that involves students achieving academic goals and life satisfaction. Hierarchical regressions examined the role of six psychosocial factors for college success among 579 first-year college students. Academic self-efficacy and organization and attention to study were predictive of first semester grade point average (GPA) when controlling relevant demographic factors. Academic self-efficacy was even predictive of end-of-year GPA when controlling previous, first-semester GPA. Mediation analyses revealed that first-semester GPA was an important mediator between these two psychosocial variables and end-of-year GPA. Additional psychosocial variables were predictive of college students’ life satisfaction: stress and time management, involvement with college activity, and emotional satisfaction with academics. We explore how formulating interventions on the basis of psychosocial factors offers an avenue for students to address specific attitudes, emotions, and behaviors that relate to college success.
Keywords: College success; First-year college students; Freshmen